Water Fraction of Beetroot (Beta Vulgaris L.) as Antilipemic in Swiss Webster Male White Mice - Indriati, Gustina; Ruth Rize pAAS Megahati S (RADINKA JAYA UTAMA PUBLISHER, 2025)
This research was motivated by whether the water fraction of beets can reduce total cholesterol levels in male Swiss Webster white mice. The aims of this study were: to determine the effect of giving beetroot water fraction in reducing total cholesterol levels of male Swiss Webster white mice; Knowing the most optimum dose of tuber water fraction variation in reducing total cholesterol levels of male Swiss webster white mice compared to simvastatin. The method used in this study was experimental research using Swiss Webster male white mice as test animals. The beetroots used for the research were beetroots with the criteria of 2,900 grams per tuber weighing 200-250 grams. Completely Randomized Design (CRD) with 5 treatments and 5 replications. The data obtained was processed statistically using SPSS to determine the effect of the water fraction of beets on reducing total cholesterol levels which were analyzed using the ANOVA test. The results obtained in this study were (1) The water fraction of beets had activity in reducing total cholesterol levels in male Swiss webster white mice. (2) Statistical test results of the beetroot water fraction showed that dose III (6.980 mg/20g BW) had the most optimum antilipemic activity compared to dose I (1.742 mg/20g BW) and dose II (3.484 mg/20g BW). Conclusion: The results of statistical tests of the water fraction of beetroot showed that dose III (6,980 mg/20g BW) had the most optimal antilipemic activity compared to dose I (1,742 mg/20g BW) and dose II (3,484 mg/20g BW).